THE ROLE OF INSTITUTIONAL REFORMS IN STRENGTHENING THE STABILITY OF THE INVESTMENT ENVIRONMENT - Yusupdjanova Nargiza Utkirovna; Karimov Inomjon Ortikbayevich (Journals Park Publishing, 2025)
This article analyzes the role of institutional foundations in ensuring the stability of Uzbekistan’s investment policy. It examines the essence and implementation mechanisms of investment policy as well as the legal and organizational frameworks established by the government. The study explores the dynamics of fixed capital investments across regions and highlights the importance of institutional reforms in improving the investment climate. The findings indicate the need to further strengthen legal, organizational, and economic mechanisms to stabilize investment processes.
Keywords: Investment policy, institutional reforms, fixed capital, economic stability, investment climate, legal framework.